Dataset on the folic acid uptake and the effect of sonication-based fortification on the color, pasting and textural properties of brown and milled rice - Tiozon, Rhowell N.; Camacho, Drexel H.; Bonto, Aldrin P.; Oyong, Glenn G.; Sreenivasulu, Nese (Elsevier, 2020)
The data included in this article are related to research paper entitled “Efficient fortification of folic acid in rice through ultrasonic treatment and absorption”. These datasets compile the folic acid uptake expressed in concentration and the effects of folic acid fortification on the physical properties of brown and milled rice. We reported the folic acid uptake of rice in increasing fortificant concentration through soaking, one-step, and stepwise fortification protocols. In addition, the data on the effects of fortification on the color, pasting, and textural properties of brown and milled rice were also presented.